Sport in the Asia-Pacific region - Alan Bairner; Jung Woo Lee; Tien-Chin Tan (2016)
Despite the influence of Confucianism, with its emphasis on intellectual rather than physical activity, throughout much of east and south-east Asia, sport has acquired a prominent role in most, if not all, countries in the region. This chapter provides an introduction to the role of sport in four East Asian countries – Japan, Taiwan, the People’s Republic of China, and South Korea. It does so by focusing on three main issues, each of which has relevance, albeit to varying degrees, for the countries under discussion. These are the relationship between sport, national identity and nationalism, the significance, or otherwise, of traditional games and/or national sports within the context of globalization, and the role of sports mega-events in relation to modernization.